Remittance flows and U.S. monetary policy - Immaculate Machasio; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2021)
Remittance inflows are driven by macroeconomic conditions in the home and the host economies, respectively. In this paper, we study the effect of U.S. monetary policy on remittance flows into economies in Latin American and the Caribbean. The role of Fed policy for remittances has not yet been studied. We estimate a series of panel local projections for remittance inflows into eight countries. A surprise change in U.S. monetary conditions has a strong and highly significant negative effect on inflows. Our finding remains robust if we change the sample period or include additional variables. Hence, our paper establishes a remittance-channel through which the Fed affects the business cycle abroad.
Keywords: F24; F41; E52; O11; 330; remittances; migration; business cycle; monetary policy; spillovers